A proposed adaptation of the European Foundation for Quality Management Excellence Model to physical activity programmes for the elderly - development of a quality self-assessment tool using a modified Delphi process - Marques Ana I; Santos Leonel; Soares Pedro; Santos Rute; Oliveira-Tavares António; Mota Jorge; Carvalho Joana (BMC, 2011)
Abstract Background There has been a growing concern in designing physical activity (PA) programmes for elderly people, since evidence suggests that such health promotion interventions may reduce the deleterious effects of the ageing process. Complete programme evaluations are a necessary prerequisite to continuous quality improvements. Being able to refine, adapt and create tools that are suited to the realities and contexts of PA programmes for the elderly in order to support its continuous improvement is, therefore, crucial. Thus, the aim of this study was to develop a self-assessment tool for PA programmes for the elderly. Methods A 3-round Delphi process was conducted via the Internet with 43 national experts in PA for the elderly, management and delivery of PA programmes for the elderly, sports management, quality management and gerontology, asking experts to identify the propositions that they considered relevant for inclusion in the self-assessment tool. Experts reviewed a list of proposed statements, based on the criteria and sub-criteria from the European Foundation for Quality Management Excellence Model (EFQM) and PA guidelines for older adults and rated each proposition from 1 to 8 (disagree to agree) and modified and/or added propositions. Propositions receiving either bottom or top scores of greater than 70% were considered to have achieved consensus to drop or retain, respectively. Results In round 1, of the 196 originally-proposed statements (best practice principles), the experts modified 41, added 1 and achieved consensus on 93. In round 2, a total of 104 propositions were presented, of which experts modified 39 and achieved consensus on 53. In the last round, of 51 proposed statements, the experts achieved consensus on 19. After 3 rounds of rating, experts had not achieved consensus on 32 propositions. The resulting tool consisted of 165 statements that assess nine management areas involved in the development of PA programmes for the elderly. Conclusion Based on experts' opinions, a self-assessment tool was found in order to access quality of PA programmes for the elderly. Information obtained with evaluations would be useful to organizations seeking to improve their services, customer satisfaction and, consequently, adherence to PA programmes, targeting the ageing population.